An osmesl mutant delayed rice leaf senescence through inhibiting cell death by OsBI-1 - Hu, Bin; Shen, Enlong; Zhou, Fengling; Sun, Bo; Wang, Xingchao; Zhou, Fei; Lin, Yongjun (Plant science (Limerick), 2024)
Leaf senescence following heading in rice is subject to rigorous regulation, with many of the underlying control mechanisms remaining largely unknown. In this study, we identified a novel gene, OsMESL, which exerts a positive regulatory effect on leaf senescence in rice. The T-DNA insertion mutant known as osmesl and RNA interference plants displayed a phenotype characterized by stay-green after heading. Genetic analysis indicated that the mutant phenotype could be rescued through complementation, while the overexpression of OsMESL accelerated leaf senescence after heading, underscoring OsMESL's positive regulatory role in rice leaf senescence. Subsequent investigations revealed that OsMESL modulates the process of cell death by influencing the stability of its interacting protein, the cell death suppressor OsBI-1, thereby governing leaf senescence. Furthermore, the leaves of the osmesl mutant exhibited a delayed reduction in photosynthesis, along with increased grain length and 1000-grain weight. In conclusion, we identified OsMESL as a novel positive regulator of leaf senescence in rice, which likely participates in leaf senescence through the mediation of cell death by OsBI-1, resulting in the phenotype of stay-green in the osmesl mutant after heading. •OsMESL positively regulates leaf senescence in rice.•OsMESL is necessary for OsBI-1 protein stability.•The mutation of OsMESL reduces the protein level of OsBI-1, thereby inhibiting autophagy and delaying leaf senescence.